The structure of the Student Academic Motivation Scale (SAMS-21) - Kairys, Antanas; Liniauskaitė, Audronė; Brazdeikienė, Liana; Bakševičius, Laimis; Čepienė, Ramutė; Mažeikaitė-Gylienė, Žieda; Rugevičius, Mindaugas; Žakaitienė, Aldona; Žakaitis, Povilas (Psichologija, 2017)
The Student Academic Motivation Scale (SAMS-21), which was developed on the cornerstone attitudes of the self-determination theory and hierarchical model (Vallerand, 1997; 2000), while seeking to retain the suggested structure of motivation types, is presented in this article. There are suggested seven types in the Vallerand hierarchical motivation model (Vallerand, 1997; 2000) that correspond with the original proposal from Deci and Ryan: three types of intrinsic motivation (intrinsic motivation to know, to accomplish things and to experience stimulation), three types of extrinsic motivation (external regulation, introjected and identified), and amotivation. There are some scales to evaluate academic motivation, (Hegarty, 2010; Martin, Yu, Paporth, Ginns, & Collie, 2014; Moyen & Doyle, 1978), the most popular among them is the Academic Motivation Scale (AMS; Vallerand et al., 1992). There are more than a few studies that have confirmed the scale’s validity and reliability (Cokley et al., 2001; Vallerand et al., 1992). AMS is adjusted in some countries, for example, in Croatia (Koludrović & Ercegovac, 2014), Italy (Alivernini & Lucidi, 2008), Turkey (Can, 2015) and in others. Despite the evidences of scale validity, it does have some shortages. It could be shorter; the structure of the scale is not identical with the theoretical model (Cokley, 2000; Fairchild, Horst, Finney, & Barron, 2005) and the wording of items of extrinsic introjected motivation subscales is not entirely matching the theoretical concept of introjected motivation. All those reasons, as well the opportunity to have choice of the instruments that are assessing the same construct, stimulate us to create the Student Academic Motivation Scale (SAMS-21).The aim of the research is to develop a short scale for the assessment of academic motivation and examine its structure and psychometrical properties in the sample of students. The research was conducted in two stages; 621 students that are studying in different study programs from two universities participated in it. The SAMS-21 scale was used to examine academic motivation. The Lithuanian version of the General Motivation Scale (GMS-28; Guay et al., 2003; Urbanaviciute et al., 2013) was used to evaluate the convergent and divergent validity of the SAMS-21 scale. Students were asked about their term grade averages and the satisfaction with their study programs. Obtained results confirmed the seven types of motivation that are traditionally distinguished by the authors of self-determination theories; however, the validity of second order factors (intrinsic and extrinsic motivation) was not confirmed. All subscales of SAMS-21 correlated in a statistically significant manner with corresponding GMS-28 subscales; however, a relatively higher correlation (rs = 0.74) was obtained between SAMS-21 and GMS-28 for the intrinsic motivation to know. The intrinsic motivation to experience stimulation and amotivation subscales correlated stronger not with the corresponding GMS-28 subscales, but with other GMS-28 subscales. The present findings provide adequate support for the reliability of the scale as well as the proof of scale validity.
Keywords: self-determination theory; Lithuanian academic motivation scale; academic motivation